Prevalence and factors associated with the use of modern contraceptive methods among female healthcare providers in health facilities in Guinea - Youla, Yamoussa; Sidibé, Sidikiba; GC, Hounmenou; Kourouma, Mory1; Camara, Saidouba Chérif; Bangoura, Salifou Talassone; Olivier, K. K. J. J.; Grovogui, Mathias; Diaby, Maladho; Bongono, Emile Faya; Diallo, Oumou Hawa; Conté, Ibrahima; et al. (Frontiers in Global Women's Health, 2025)
IntroductionThe low use of modern contraceptive methods by female healthcare providers is a real public health problem in Guinea. This study aimed to analyze the prevalence and factors associated with the use of modern contraceptive methods among female healthcare providers in Guinea.MethodThis was a secondary analysis of data from a cross-sectional survey on the use of modern contraceptive methods among female healthcare providers in Guinea between November 1, 2020, and January 31, 2021. The study included 1,743 women from 173 health facilities across the country.ResultsThis survey included women whose median age was 29 years, with an interquartile range of (24–39) years. Women with a higher level of education (n = 1,656; 95.5%) and a midwifery profile (n = 838; 48.3%) represented the highest proportions. Among the subjects surveyed, Muslim women were the majority (n = 1,229; 70.9%). The overall prevalence of use of modern contraceptive methods by female healthcare providers in Guinea was 61.9%; CI: 59.6–64.1). Married (aOR = 1.19; CI = 0.95–1.50), having secondary education (aOR = 7.92; CI = 3.68–20.7), women belonging to the Muslim religion (aOR = 1.37; CI = 1.09–1.71) were factors statistically associated with the use of modern contraceptive methods among female healthcare providers.ConclusionImproving the national prevalence of modern planning methods requires the involvement of stakeholders at all levels. This study's results show a progression in the implementation of governmental actions and health projects and programs related to sexual reproductive health.